Genome-wide identification of DnaJ gene family in Catalpa bungei and functional analysis of CbuDnaJ49 in leaf color formation - Yang, Yingying; Zhao, Linjiao; Wang, Junhui; Lu, Nan; Ma, Wenjun; Ma, Jiang; Zhang, Yu; Fu, Pengyue; Yao, Chengcheng; Hu, Jiwen; Wang, Nan (Frontiers in Plant Science, 2023)
DnaJs are the common molecular chaperone proteins with strong structural and functional diversity. In recent years, only several DnaJ family members have been found to be able to regulate leaf color, and it remains to be explored whether there are other potential members that also regulate this character. Here, we identified 88 putative DnaJ proteins from Catalpa bungei, and classified them into four types according to their domain. Gene-structure analysis revealed that each member of CbuDnaJ family had same or similar exon-intron structure. Chromosome mapping and collinearity analysis showed that tandem and fragment duplication occurred in the process of evolution. Promoter analyses suggested that CbuDnaJs might be involved in a variety of biological processes. The expression levels of DnaJ family members in different color leaves of Maiyuanjinqiu were respectively extracted from the differential transcriptome. Among these, CbuDnaJ49 was the largest differentially expressed gene between the green and yellow sectors. Ectopic overexpression of CbuDnaJ49 in tobacco showed that the positive transgenic seedlings exhibited albino leaves, and the contents of chlorophyll and carotenoid were significantly reduced compared with those of wild type. The results suggested that CbuDnaJ49 played an important role in regulating leaf color. This study not only identified a novel gene of DnaJ family members regulating leaf color, but also provided new germplasm for landscaping.